PENGARUH STORE ATMOSPEHER TERHADAP LOYALITAS KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL MEDIASI PADA WARUNK UPNORMAL LAMPUNG - Delviansyah Ade Patra Delviansyah; Diah Utami; Rifai Budi Hartanto; Vicky F Sanjaya (Universitas Ngudi Waluyo, 2020)
The research objective is to determine the application of store atmosphere diwarunk upnormal, to see consumer loyalty in normal warunk and for purchasing decisions as a mediation in normal warunk Lampung. This research activity was carried out at the upnormal warunk in the city of Bandar Lampung. The research method used in this journal is a questionnaire method. The sample of this research may be 93 respondents. Statistical tests were performed using Cronbach's alpha, composite reliability and Average Variance Extracted (AVE). All proposed hypotheses are supported and significant. The conclusion of this study is the effect of Store Atmosphere on loyalty has a significant and positive effect on purchase decisions as a mediating variable in the upnormal warunk Lampung.